TINJAUAN YURIDIS KEBATALAN AKTA DAN PERTANGGUNGJAWABAN NOTARIS (Studi Kasus Putusan Perkara Nomor: 10/Pdt.G/2015 PN.Dmk) - Ary Yuniastuti; Jawade Hafidz (Jurnal Akta, 2017)
Research on "Juridical Review of Notice Deed and Notary Accountability (Case Decision Case Study No. 10 / Pdt.G / 2015 PNDmk) aims to know the process of making authentic deeds made before the Notary, the juridical reasons for the occurrence of authentic authenticity deed made by a Notary Public, the responsibility of a notary against the cancellation of the authentic deed already made.In the Decision of the case registers Number 10 / Pdt.G / 2015 / PN.Dmk in the District Court Demak has stated that the notarial deed and PPAT in the event of sale and sale is declared null and void because it does not meet the form of deed as referred to in Article 38 Undang -The Republic of Indonesia Number 2 Year 2014 Concerning Amendment to Law Number 30 Year 2004 Concerning Position of Notary and contrary to Article 1320 of the Civil Code regarding the legal terms of the agreement. Deed which is declared null and void is directly related to the roles and responsibilities of a notary public, is there any relation to the negligence of a notary since in the case of the notarial deed which plays the role of a deed determined by law is notary as an official authorized by law .Keywords: Notary Deed, Reason for Deed of Deed, Liability of Notary.